2003
DOI: 10.1002/chin.200332172
|View full text |Cite
|
Sign up to set email alerts
|

Tetralone Acids as Intermediates for the Synthesis of Podophyllotoxin Analogues.

Abstract: For Abstract see ChemInform Abstract in Full Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The title compound, (I), a benzophenone derivative, is an intermediate for the preparation of antimitiotic -apopicropodophyllin (Basavaraju & Anjanamurthy, 2003). Over 300 crystal structures of benzophenone derivatives in the Cambridge Structural Database (CSD, Version 5.26;Allen, 2002) highlight the importance of structural studies on such pharmaceutically useful compounds.…”
Section: Commentmentioning
confidence: 99%
“…The title compound, (I), a benzophenone derivative, is an intermediate for the preparation of antimitiotic -apopicropodophyllin (Basavaraju & Anjanamurthy, 2003). Over 300 crystal structures of benzophenone derivatives in the Cambridge Structural Database (CSD, Version 5.26;Allen, 2002) highlight the importance of structural studies on such pharmaceutically useful compounds.…”
Section: Commentmentioning
confidence: 99%
“…In view of the above facts, it was decided to modify the structure of podophyllotoxin and synthesized tetralone acids as analogues [5][6][7][8]. They were synthesized by replacing 3,4,5-trimethoxyphenyl ring with cyclohexyl group in podophyllotoxin and 1,3-methylene dioxy ring with methoxy, methyl, thiomethyl group and hydrogen and fluorine elements and lactone ring with carboxylic acid group.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that α-tetralones are the basic units of several tricyclic or tetracyclic natural products. 1,2 Notable work has been done by Vasavaraju et al 3 who have prepared some substituted tetralones and used them to construct various tricyclic products. In that particular work they have also reported the antimitotic activity of tetralones.…”
mentioning
confidence: 99%
“…After that, until now, very little work has been reported on the efficient synthesis of tetralones. 1,3 In most cases, the routes are lengthy and are not general. An emerging group of antibiotics popularly known as angucyclines, active antitumor agents, in most cases contain a tetralone as one of the basic units.…”
mentioning
confidence: 99%